Nurse’s Viewpoint of Gatekeeper Function on Managing Indonesian National Health Insurance: A Qualitatif Study - Della Kharisma Putri; Nurfika Asmaningrum; Alfid Tri Afandi (KHD-Production, 2022)
WHO initiated a policy related to the health for all principles and realized it in the application of gatekeeper theory for increasing the quality of public health center services which include the aspects of First Contact, Continuity, Comprehensiveness, and Coordination services. The purpose of this research was to explore nurses’ perceptions of gatekeepers’ role in NhI services at Public Health Center. This research is using descriptive qualitative design and purposive sampling with thematic analysis is used as sampling technique. Characteristics of the participants include 80% female with qualification 80% are vocational nurses and 60% nurses on duty at community public health center. Results of this research found three major themes including the involvement of administrative services, service providers, and service strategy implementers. The three themes are a manifestation of the integration of implementation of the four main gatekeeper functions by nursing staff of Public Health Center. Services run by nurses are considered less than optimal in first contact and continuous aspect, in term of nursing care documentation and the absence of HIV/AIDS treatment services. This research is expected to be a guide for updating information related to the role of nurses in public health center as gatekeeper. Keywords: NhI, gatekeeper, nurses, public health center, qualitative